TINJAUAN LOCA (LETTER OF OPERATIONAL AND COORDINATION AGREEMENT) ANTARA HANG NADIM TOWER DAN TANJUNG PINANG APPROACH TERHADAP PELAYANAN LALU LINTAS UDARA DI PERUM LPPNPI KANTOR CABANG BATAM - Siti Auliyana Amany; Wasito Utomo; Arnaz Olieve (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Batam Hang Nadim International Airport is an airport that has the longest runway in Indonesia, which is 4025 m long and 45 m wide. Batam Hang Nadim International Airport has approximately 110 aircraft movements per day. With the large number of aircraft movements, in terms of air traffic services, it is required to be able to provide maximum service so as to create a smooth flow of air traffic. However, this has not been maximized because the transfer of control of arrival aircraft from Tanjung Pinang Approach to Hang Nadim Tower is not in a definite position and can cause ambiguity when coordinating. The theories supporting this research include ICAO Annex 11, ICAO Chapter 6 point 6.5 (Procedures for Arriving Aircraft), CASR 170 PM 65 of 2017 (Air Traffic Rules), ICAO DOC. 4444 (Air Traffic Management), KP 41 of 2020, LOCA Batam and Tanjung Pinang. Data was collected by means of observation, questionnaires, and literature study. The results show that the Transfer of Control of arrival aircraft from Tanjung Pinang Approach to Hang Nadim Tower is less efficient. A review is needed in the TOC of arrival aircraft and the naming of IAF points in the IAC which can facilitate the transfer of arrival aircraft and at a definite point.